Synonyms : French fries and chips and other words that mean the same thing but look and sound as different as truck and lorry - Hanson, Joan. (Minneapolis : Lerner Publ. Co., 1972)
Two illustrations of the same object with varying detail reflect the identical meaning of the British and American words for the same thing.
Keywords: English language -- Synonyms and antonyms -- Juvenile literature; English language -- Synonyms and antonyms